Motivations for News Exposure in Different Media Systems: A Comparative Study of Germany, Spain and the United Kingdom - Rodríguez-Virgili, Jordi; Sierra, Aurken; Serrano-Puche, Javier (Communication Today, 2022)
The purpose of the study is to examine and compare digital users’ motivations for news exposure in three European countries (Germany, Spain, and the United Kingdom) belonging to each of Hallin and Mancini’s media systems. For this research, a cross-national online survey (2020) of over 2,000 people in each country was used. The users’ assessment of the preferences for getting news (from sources that share, challenge or do not have a particular point of view) was analysed, as well as the influence of socio-demographic factors and interest in politics on those motivations. Our results show that a majority of digital users prefer unbiased news. With respect to the socio-demographic variables, a clear pattern can be discerned in the age variable, whereby the older they are, the greater the declared preference for unbiased news. On the other hand, those who show greater interest in politics do prefer reinforcing news. In terms of national differences, motivations for news exposure vary depending on the country studied. In Spain, in line with its belonging to the pluralist-polarised system, the preference for reinforcing news is higher than in Germany and in the United Kingdom.